Teaching Dobbs to Disrupt U.S. Hegemony and Build Feminist Solidarities - Siegel, Derek P. (Radical Teacher, 2024)
The Dobbs decision has created both opportunities and challenges in the classroom. On one hand, Dobbs animated student interest, increasing awareness of reproduction. On the other hand, media coverage of Dobbs primed students—particularly those who had not been exposed to reproductive justice—to think about abortion access in isolation from other topics and from an exclusively U.S. perspective. In this article, I discuss my experience teaching the Politics of Reproduction in Fall 2022. Among other goals, I wanted to expose students to La Marea Verde, or the “Green Wave,” of countries expanding abortion access in Latin America. By teaching Latin American abortion politics in relation to the Dobbs decision, I aim to disrupt U.S. hegemony. Specifically, teaching about the Green Wave highlights the possibility of organizing for reproductive justice outside the parameters of the state and challenges the logic of American Exceptionalism, which works to justify and normalize intersectional inequalities. I’d like to thank Dr. Laura Briggs & the Five College Reproductive Health, Rights, and Justice (RHRJ) certificate program for their invaluable support developing the syllabus this article is based on (<a id="OWA00f0d75b-5fe7-c122-91a7-85bdd7c4eaa0" title="Original URL: https://www.fivecolleges.edu/academics/reproductive-health-rights-justice. Click or tap if you trust this link." href="https://nam12.safelinks.protection.outlook.com/?url=https%3A%2F%2Fwww.fivecolleges.edu%2Facademics%2Freproductive-health-rights-justice&data=05%7C02%7Crlh52%40pitt.edu%7Cac28a8ca95a8407d45d008dcfa78a197%7C9ef9f489e0a04eeb87cc3a526112fd0d%7C1%7C0%7C638660644175345397%7CUnknown%7CTWFpbGZsb3d8eyJWIjoiMC4wLjAwMDAiLCJQIjoiV2luMzIiLCJBTiI6Ik1haWwiLCJXVCI6Mn0%3D%7C0%7C%7C%7C&sdata=DP9tDvWw6hGKskOVQNGpMswt9ukFZk4p2K%2FlMZqEOHU%3D&reserved=0" data-auth="Verified" data-linkindex="0">https://www.fivecolleges.edu/academics/reproductive-health-rights-justice). Dr. Briggs developed an original syllabus for the Politics of Reproduction with a grant from the RHRJ program, encouraging me to adopt a similarly transnational approach to this course (little did I know how important such an approach would be in the post-Dobbs classroom). While the activities I discuss in this article are my own, the structure of the syllabus is based on Dr. Briggs’, and the arguments I make would not be possible without the robust community of feminist and reproduction scholars within and outside the RHRJ program. The funding I also received from the RHRJ certificate program provided stipends for the invited guest speakers.